ANALYSIS OF THE DISTRIBUTION OF SALINITY VALUE AND SEA SURFACE TEMPERATURE IN LAMONG BAY WATERS, GRESIK REGENCY - Maulana Yusuf; Hendrata Wibisana; Siti Zainab (CI-TECH, 2021)
The waters of Teluk Lamong are located on the north sea coast of Surabaya, which is directly adjacent to the Gresik Regency. Lamong Bay is famous as a strategic port place on an International scale. Along the coastal waters of Teluk Lamong, some rivers flow in Lamong Bay. These activities can lead to interaction between fresh water and seawater. This interaction affects the pattern of salinity spread and sea surface temperature in the waters of Teluk Lamong. Salinity and Sea Surface Temperature is one of the biggest factors causing corrosion in the sea that will damage the structure of buildings around the sea. It is expected that in this research as information about the waters of Teluk Lamong for data information or database utilization in the field of civil engineering, among others, port maintenance and coastal building planning. Based on this background, research is needed to monitor the spread of salinity values and sea surface temperatures in Lamong Bay using Landsat 8 satellite imagery for the years 2016 and 2020. The result of modeling the algorithm obtained, the model of the algorithm used to process the salinity of the image is the wavelength Band_4 in the Equation Power with the model algorithm y = 25.437x-0.046, and the degree of determination value R² = 0.5825. While sea surface temperature in power equation with algorithm model y = 302.14x0.0029 and determination value R² = 0.4182. The results of an analysis of the T-test and validation test can be qualified. The results of the analysis of imagery data showed salinity distribution ranged from 27.33 (ppm) to 29.9 (ppm), while sea surface temperatures ranged from 303.95 Kelvin to 304.39 Kelvin.